War and city-making in Somalia: Property, power and disposable lives. (August 2019) - Bakonyi, Jutta; Chonka, Peter; Stuvøy, Kirsti
Abstract: Rapid urbanisation in Somalia, as in many other war-torn countries, is driven by in-migration of displaced people who are often amassed in camps. Although such camps become institutionalised sites of exclusion where 'bare life' is generated and disposed, they are also characterised by socially messy and continuously evolving relations of space, power, violence and displacement. The article draws on fieldwork with displaced people in Somali cities to analyse claims to property and (often violent) competition to uphold them in contestation for sovereignty. Comparing two cities, Mogadishu and Bosaaso, we show how a broad range of international and local actors, including displaced people themselves, negotiate (urban) property and establish relations that guide and foster political authority, while rendering the lives and livelihoods of displaced people precarious and insecure. In property, politics and the economy intersect, and property relations are therefore subject to struggles for both power and profit. We underscore how sovereign power produces spaces of indistinction, but emphasise that property as an analytical category contributes to understandings of sovereignty. Furthermore, propertying as social practice draws attention to the way sovereignty emerges and is connected to the market. This enables the differentiations of forms of sovereignty and draws attention to how it is negotiated, openly challenged or silently undermined.